Dual Network Hydrogels Incorporated with Bone Morphogenic Protein-7-Loaded Hyaluronic Acid Complex Nanoparticles for Inducing Chondrogenic Differentiation of Synovium-Derived Mesenchymal Stem Cells - Qing Min; Jiaoyan Liu; Yuchen Zhang; Bin Yang; Ying Wan; Jiliang Wu (Pharmaceutics, 2020)
Alginate-poloxamer (ALG-POL) copolymer with optimal POL content was synthesized, and it was combined with silk fibroin (SF) for building ALG-POL/SF dual network hydrogels. Hyaluronic acid(HA)/chitosan-poly(dioxanone)(CH-PDO) complex nanoparticles (NPs) with optimized composition and high encapsulation efficiency were employed as a vehicle for loading bone morphogenic protein-7 (BMP-7). BMP-7-loaded HA/CH-PDO NPs were incorporated into ALG-POL/SF hydrogel for constructing composite gels to achieve controlled release of BMP-7. These gels showed thermosensitive sol-gel transitions near physiological temperature and pH; and they were tested to be elastic, tough and strong. Some gels exhibited abilities to administer the BMP-7 release in nearly linear manners for a few weeks. Synovium-derived mesenchymal stem cells (SMSCs) were seeded into optimally fabricated gels for assessing their chondrogenic differentiation potency. Real-time PCR analyses showed that the blank ALG-POL/SF gels were not able to induce the chondrogenic differentiation of SMSCs, whereas SMSCs were detected to significantly express cartilage-related genes once they were seeded in the BMP-7-loaded ALG-POL/SF gel for two weeks. The synthesis of cartilaginous matrix components further confirmed that SMSCs seeded in the BMP-7-loaded ALG-POL/SF gel differentiated toward chondrogenesis. Results suggest that BMP-7-loaded ALG-POL/SF composite gels can function as a promising biomaterial for cartilage tissue engineering applications.